OPTIMALISASI PEMBELAJARAN MELALUI TEORI PEMROSESAN INFORMASI - Sefrinal Sefrinal; Imratul Handayani; Hilyati Fadhilah; Annisa Elvina (STKIP Pesisir Selatan, 2026)
A learner's success is determined less by the amount of information received than by how that information is processed, stored, and retrieved when needed. This article examines information processing theory as a framework for understanding the cognitive processes of learning and for explaining why students forget. Using a library research method, it reviews verified books and scholarly journal articles published within the last ten years. The findings show that learning unfolds through a sequence of cognitive stages sensation, attention, encoding, storage, and retrieval strongly shaped by the limited capacity of working memory. Forgetting is understood not merely as failure but as an active process driven by encoding failure, trace decay, interference, and weak retrieval cues. Strategies such as chunking, multimodal instruction, elaborative rehearsal, and constructive feedback effectively manage cognitive load and strengthen retention. The article concludes that teachers' understanding of human cognitive architecture is foundational for designing effective, meaningful, and learner-centered instruction.